Higher Angiotensin II Type 1 Receptor Levels and Activity in the Postmortem Brains of Older Persons with Alzheimer's Dementia. Issue 4 (16th December 2021) - Cosarderelioglu, Caglar; Nidadavolu, Lolita S; George, Claudene J; Marx-Rattner, Ruth; Powell, Laura; Xue, Qian-Li; Tian, Jing; Salib, Joy; Oh, Esther S; Ferrucci, Luigi; Dincer, Pervin; Bennett, David A; et al.
Abstract: Aging is a key risk factor in Alzheimer's dementia (AD) development and progression. The primary dementia-protective benefits of angiotensin II subtype 1 receptor (AT1 R) blockers are believed to arise from systemic effects on blood pressure. However, a brain-specific renin-angiotensin system (b-RAS) exists, which can be altered by AT1 R blockers. Brain RAS acts mainly through 3 angiotensin receptors: AT1 R, AT2 R, and AT4 R. Changes in these brain angiotensin receptors may accelerate the progression of AD. Using postmortem frontal cortex brain samples of age- and sex-matched cognitively normal individuals ( n = 30) and AD patients ( n = 30), we sought to dissect the b-RAS changes associated with AD and assess how these changes correlate with brain markers of oxidative stress, inflammation, and mitochondrial dysfunction as well as amyloid-β and paired helical filament tau pathologies. Our results show higher protein levels of the pro-inflammatory AT1 R and phospho-ERK (pERK) in the brains of AD participants. Brain AT1 R levels and pERK correlated with higher oxidative stress, lower cognitive performance, and higher tangle and amyloid-β scores. This study identifies molecular changes in b-RAS and offers insight into the role of b-RAS in AD-related brain pathology.